A rare case of primary vaginal carcinoma with systemic metastasis with uterovaginal prolapses - Damineni, Sree Chandana; K., Shraddha Shetty (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Primary vaginal cancer in a prolapsed uterus is a very rare condition. Here we report a rare case of carcinoma of vagina with early systemic metastasis presenting in a middle aged women with uterovaginal prolapse. A 46 year old postmenopausal lady presented with complaints of mass per vagina with foul smelling discharge per vagina. On gynaecological examination, an irreducible uterovaginal prolapse and a 6 × 6 cm ulcer was present on upper 1/3 of lateral vaginal wall. Biopsy of the ulcer suggested squamous cell carcinoma of vagina. She was given palliative chemotherapy.